2000
DOI: 10.1097/00006254-200004000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Interval Delivery in Multiple Pregnancies. Is Optimism Justified?

Abstract: Acta Obstet Gynecol Scand 1999; 78: 710-715. C Acta Obstet Gynecol Scand 1999 Objective. Evaluation of the success of delayed interval delivery in multiple pregnancies. Method. Retrospective analyses of all multiple pregnancies with the birth of one child at a gestational age of 16-31 weeks (nΩ80). Three groups were defined: group I, unsuccessful attempt to temporize delivery, group II, interval between the first child and the other child or children 3 hours or more, with delivery of the remaining children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…CRP is considered as good prognostic index for incipient chorioamnitis. 1,6,12 As repeated high vaginal swab culture and sensitivity came to positive for Klebsiella infection in spite of treatment. We have stopped antibiotics and kept her under coverage of probiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP is considered as good prognostic index for incipient chorioamnitis. 1,6,12 As repeated high vaginal swab culture and sensitivity came to positive for Klebsiella infection in spite of treatment. We have stopped antibiotics and kept her under coverage of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In our case as there was no evidence of intrauterine infection hence administration of steroid is beneficially. 12 She entered into labour at 31 weeks after a latent period of 70 days which is significant.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the gestational age at the fi rst delivery was 17-26.5 (median 23) weeks. Arias et al [26] and Seince et al [28] propose a limit gestational age of 28 weeks, van Doorn et al [29] and Kalchbrenner et al [25] 30 weeks, Farkouh et al [3] 31 weeks and Porreco et al [24] 32 weeks. Abboud et al [6] and De Jong et al [27] demonstrated a trend to better outcome for the second twin when the fi rst was delivered earlier in pregnancy.…”
Section: Commentmentioning
confidence: 99%
“…The mean latency interval tends to be longer among women with cerclage, although statistical analysis is not possible with all cases because of various protocols ( fi g 2 ). A study [32] case series using the same protocol [3,17,25,26,29,33] suggests that cerclage after the fi rst delivery is associated with a longer inter-delivery interval without increasing the risk of intrauterine infection. Knight et al [9] propose cervix ultrasonographic monitoring to indicate a cerclage in case of persistent dilatation.…”
Section: Commentmentioning
confidence: 99%
“…Modem management procedures, including tocolytics, corticosteroids, antibiotics and cervical cerclage would appear to be important in the overall success of treatment in a retained twin. Although both tocolytics and cerclage appear to prolong the mean delivery interval, no statistical difference in survival was found concerning cerclage, antibiotic therapy, tocolysis and hospitalization (I, [3][4]. The use of prolonged bed rest, cervical cerclage, tocolysis, antibiotics and corticosteroids compose complex, frequently debatable issues.…”
mentioning
confidence: 99%